Serum Ferritin: As a Biomarker in Diagnosis of Dengue Fever - Zia Ul Ain Sabiha, Hafsa Tariq, Rabeea Zia, K. Suresh Babu, Inam-U-Llah, Rehana Rasool, Sudhair Abbas Bangash, Safdar Ali, Mahnoor, Irfan Ullah (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Major public health risk was ‘Dengue infection’ initial discovery is critical to improving the existence in serious infection of dengue. Our objective in this study was to investigate the serum ferritin level to suppose biomarker in the diagnosis of dengue fever. Method: An observational and prospective study was conducted in the Hayatabad Medical Complex and it included one hundred nineteen cases related to dengue was diagnosed by using NSI Test antigen or serology test related to specific dengue that internment “ELISA”. At the time of diagnosis, serum ferritin was measured. Monitoring the clinical and platelets counts was done on daily bases, it also classified into two groups such as non-severe and severe groups by allowing WHO criteria in 2009. Result: Five out of 119 cases of dengue were severe, dengue patients had lower platelets when they are in severe condition, count the number of platelets (p less than 0.0001); Ferritin level almost high (p=0.02) and the value of hospital longer time period (p less than 0.0001) mostly in severe group as compare to non-severe group of dengue. Platelets count had negative value with age factor almost Positive correlations with ferritin levels (p=0.08 or r= 0.16) and a longer hospital stay (r= -0.427 and p 0.0001) were also found (r= 0.26, p= 0.004). These values indicate the severe risk of dengue infection/ disease. Negative value of serum ferritin that are related to the value of platelets (r=0.51 and p< 0.001). On day 4 of clinical infections, an elevated value of ferritin is seen in severe cases. Conclusion: In Clinical practice, a biomarker for determining the severity of dengue infection is increased serum ferritin concentrations. Keywords: Biomarkers, Serum ferritin, Severity, Dengue infection, Predicators